Analysis of the function of the N1 subdomain of MSCRAMMs of Staphylococcus aureus - McCormack, Niamh (Trinity College (Dublin, Ireland). Department of Microbiology, 2014)
The Microbial Surface Component Recognising Adhesive Matrix Molecules (MSCRAMMs) family of cell wall-associated proteins have recently been reclassified based on structure-function analysis. Under this new regime the MSCRAMM family is defined by the presence of at least two tandemly-linked IgG-like folded domains. Clumping factor A (ClfA) is the archetypal fibrinogen-binding MSCRAMM of Staphylococcus aureus and an important virulence factor. An N-terminal signal sequence directs export by the Sec pathway and the C-terminal cell wall-anchoring domain allows covalent attachment of ClfA to peptidoglycan by sortase. Region A of ClfA comprises three independently folded subdomains N1, N2 and N3. Subdomains N2N3 comprise IgG-like folds and promote fibrinogen binding. However the function of subdomain N1 has, until now, remained elusive.
Keywords: Microbiology, Ph.D.; Ph.D. Trinity College Dublin